2020
DOI: 10.3390/cancers12082139
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Digital PCR to Detect Amplifications of Specific Androgen Receptor Loci in Cell-Free DNA for Prognosis of Metastatic Castration-Resistant Prostate Cancer

Abstract: Amplification of androgen receptor (AR) is a common genomic event in metastatic castration-resistant prostate cancer (mCRPC). To evaluate the prognostic value of the amplifications of specific loci in the AR gene in cell-free DNA, we developed a multiplex digital PCR (dPCR) assay that targeted AR enhancer (AR-En), AR exon 1 (AR-E1), AR exon 8 (AR-E8) and OPHN1 (downstream of AR). We selected three relatively stable genes, C2orf16, FAM111B, and GRIA3, as reference controls for copy number normalization. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our results revealed that the expression of OPHN1 may promote cancer survival and invasion. Thus, the expression of OPHN1 could promote PCa progression, which is consistent with certain other studies on PCa ( 12 , 43 ). In addition, in gastric cancer, Dicken et al revealed that the expression of OPHN1 was related to lymphovascular invasion ( 44 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that the expression of OPHN1 may promote cancer survival and invasion. Thus, the expression of OPHN1 could promote PCa progression, which is consistent with certain other studies on PCa ( 12 , 43 ). In addition, in gastric cancer, Dicken et al revealed that the expression of OPHN1 was related to lymphovascular invasion ( 44 ).…”
Section: Discussionsupporting
confidence: 92%
“…The most common genomic aberrations identified in PC are AR copy number variations (CNV), specifically AR amplification, and AR point mutations [ 67 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. A meta-analysis of 16 studies representing more than 1000 patients found that AR gain is associated with a shorter PFS and OS in patients treated with ARSi, but it had no effect in patients treated with docetaxel in the first line or cabazitaxel in the second or third lines [ 80 ].…”
Section: Liquid Biopsy As a Predictive Biomarkermentioning
confidence: 99%
“…AR amplification correlates with castration resistant prostate cancer (CRPC) and is found in approximately 20–60% of PC recurring during ADT while very rare in primary PC (<1%) [ 2 ]. Variation in detection frequency is attributed to varying patient cohorts and detection techniques with varying sensitivity and specificity using various biopsies [ 3 , 4 , 5 , 6 , 7 ]. AR amplification has commonly been associated with resistance developing against the third line ADT drug enzalutamide, which is a current therapy option for advanced PC patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%